TALLY CCL POWER OF SIMPLICITY - SINGH SHRADDHA; NAVNEET MEHRA (NEW DELHI V & S PUBLISHERS, 2025)
The book "Tally ERP 9" by Shraddha Singh provides an in-depth, easy-to-understand guide to working with Tally.ERP 9, the latest ERP software by Tally. It starts with basic accounting concepts for beginners and covers all essential topics like creating a company, adding godowns, stock items, ledger accounts, and more. The book also explains the Payroll Inventory System and related entries clearly, and introduces the basics of Tally.NET. With lots of examples and illustrations, it is especially useful for commerce students and anyone wanting practical knowledge of Tally.ERP 9.
TALLY.ERP9
ACCOUNTING
BBA & MBA
Keywords: ACCOUNTING; MANAGEMENT